CEO Experience and Commercial Banks’ Performance in Malaysia–Evidence from Inside, Outside and Total Working Experience - Chua, Mei-Shan; Roslen, Siti Nurhidayah; Nizar, Nurhuda; Mohd Ruslan, Rafiatul Adlin (Information Management and Business Review, 2023)
This paper examines the CEO experience’s impact on commercial bank performance in Malaysia from 2016 to 2021. Using the fixed effect model, we find that more experienced CEOs have more incredible abilities to overcome the complexity of the banking environment, hence, improving commercial banks’ performance. Specifically, the CEO, with experience working within and outside the bank (Total Working Experience), strengthens the financial performance of commercial banks. Furthermore, the CEO with working experience outside the banks has more pronounced effects in improving the banks’ performance than those with experience within the banks, in which an increase of one unit of working experience enhances the bank’s performance by 102% for the former and 100% for the latter. The resource dependency theory supports the findings. Based on the findings, the results suggest the importance of the CEO experience as a determinant of commercial bank performance in Malaysia. This paper provides insight into the policymakers responsible for appointing the CEOs of the banks.